Pengaruh Struktur Kekerabatan Karo (Merga, Kuta, Kalimbubu, Anak Beru, Sembuyak) Terhadap Implementasi Hukum Waris Islam - Pane, Agnes; Hadiningrum, Sri; Siahaan, Parlaungan G; Manalu, Irga S F; Fadilla, Nur; Pangaribuan, Rio O; Manalu, Rohana (CV. Rayyan Dwi Bharata, 2025)
This research focuses on legal pluralism in Indonesia, where the Karo kinship structure (Daliken Si Telu), which includes Merga, Kuta, Kalimbubu, Anak Beru, and Sembuyak, interacts with Islamic inheritance law in the inheritance practices of the Karo Muslim community, creating potential tension between patrilineal customary norms (which prioritise men as inheritors of communal assets) and Islamic faraid provisions (which guarantee women's inheritance rights). The aim of this research is to analyse the influence of these kinship structures on the implementation of Islamic inheritance law, examine the process of adaptation and negotiation between the two legal systems, and evaluate the role of customary leaders and religious scholars in harmonisation. Using a legal-anthropological approach and descriptive qualitative methods, data was collected through participatory observation, in-depth interviews with IMKA UNIMED students, and analysis of customary and legal documents in Medan. The results of the study reveal that: (1) Karo kinship structures influence inheritance distribution through the separation of property categories immovable property (kuta land, traditional houses) is retained within the merga system for male children, while movable property (savings, livestock) is distributed according to Sharia law; (2) harmony is achieved through customary deliberation (runggu) involving customary leaders and religious scholars to formulate a ‘dual track’ agreement, as well as a benefit-sharing mechanism for communal assets; (3) customary leaders and religious scholars act as key mediators bridging customary values and Sharia law, resulting in notarised minutes formalised in the Religious Court. The research conclusion affirms that the interaction between the Karo kinship system and Islamic inheritance law is not a diametric conflict, but rather a dynamic negotiation process that combines cultural preservation with gender justice through the active role of local actors.